Evaluating Patterns of Building Envelope Air Leakage with Infrared Thermography - Milad Mahmoodzadeh; Voytek Gretka; Stephen Wong; Thomas Froese; Phalguni Mukhopadhyaya (Energies, 2020)
The next-generation performance-based building energy codes are focusing on minimizing building envelope air leakage. The quantification of air leakage in buildings is typically performed with a blower door test. However, this test does not provide information about the locations of air leakage. The aim of this study is to demonstrate a method involving qualitative and quantitative components that can be used to characterize locations of air leakage with infrared thermography. Since air leakage can have a significant impact on building energy consumption in cold climates, like in Canada, this approach can quickly inform where air barrier discontinuities occurred during construction or where to selectively target air sealing efforts in existing buildings. The observations from this study are presented, based on a thermographic image analysis during a depressurized blower door test at various pressures, in an attempt to quantify the relative rates of air leakage. The results from the investigation showed that infrared thermography (IRT) was able to discern locations and infer relative ratios of air leakage. The qualitative analysis showed that areas of air leakage are more evident under higher pressure difference. The quantitative approach showed that a minimum of 25 Pa pressure difference was required to detect the air leakage in the vicinity of the window frame, as the surface temperature decreased rapidly (almost 60% of the indoor surface/outdoor air temperature difference) at this pressure. A temperature index was defined to prioritize the areas of air leakage for retrofitting purposes. Furthermore, a thermal image subtraction method was used to determine the characteristics of the cracks based on thermal patterns. Finally, the practical implication of this study, for building developers, home inspectors, property mangers, and homeowners, is the early detection of air leakage for both existing and newly constructed buildings which could result in energy and cost savings.